The role of carbohydrates in seed germination and seedling establishment of Himatanthus sucuuba, an Amazonian tree with populations adapted to flooded and non-flooded conditions - Ferreira, Cristiane Silva (2009)
Background and Aims In the Amazonian floodplains plants withstand annual periods of flooding which can last 7 months. Under these conditions seedlings remain submerged in the dark for long periods since light penetration in the water is limited. Himatanthus sucuuba is a tree species found in the 'várzea' (VZ) floodplains and adjacent non-flooded 'terra-firme' (TF) forests. Biochemical traits which enhance flood tolerance and colonization success of H. sucuuba in periodically flooded environments were investigated. Methods Storage carbohydrates of seeds of VZ and TF populations were extracted and analysed by HPAEC/PAD. Starch was analysed by enzyme (glucoamylase) degradation followed by quantification of glucose oxidase. Carbohydrate composition of roots of VZ and TF seedlings was studied after experimental exposure to a 15-d period of submersion in light versus darkness. Key Results The endosperm contains a large proportion of the seed reserves, raffinose being the main non-structural carbohydrate. Around 93% of the cell wall storage polysaccharides (percentage dry weight basis) in the endosperm of VZ seeds was composed of mannose, while soluble sugars accounted for 2·5%. In contrast, 74% of the endosperm in TF seeds was composed of galactomannans, while 22% of the endosperm was soluble sugars. This suggested a larger carbohydrate allocation to germination in TF populations whereas VZ populations allocate comparatively more to carbohydrates mobilized during seedling development. The concentration of root non-structural carbohydrates in non-flooded seedlings strongly decreased after a 15-d period of darkness, whereas flooded seedlings were less affected. These effects were more pronounced in TF seedlings, which showed significantly lower root non-structural carbohydrate concentrations. Conclusions There seem to be metabolic adjustments in VZ but not TF seedlings that lead to adaptation to the combined stresses of darkness and flooding. This seems to be important for the survival of the species in these contrasting environments, leading these populations to different directions during evolution.